2021
DOI: 10.1002/app.50790
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of reactive self‐adhesive branched polyurethane dispersant for textile pigment printing

Abstract: A series of reactive branched polyurethane dispersants (BPUs) were successfully synthesized based on epoxy as reactive group and nitrogen-containing heterocycles as anchoring group. The branched polyurethane was adopted an ''A 2 + B 3 '' approach with diisocyanate prepolymer and trimethylolpropane. The structure, molecular weight, and thermodynamic property of BPUs were characterized. The pigment dispersions were prepared with BPUs as the dispersant by ball milling, and then the characteristic parameters such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Figure 1b and Figure S5, Supporting Information, show that the NHP sample displays a particle size with an average diameter of around 50 nm, while for NHS, the nanosheets‐like Ni‐HITP is constructed in an interwoven pattern (Figure 1c). After the pore engineering of ball‐milling treatment, the size of NHP decreases obviously, [ 14 ] smaller than 10 nm, and meanwhile a unique Tostadas‐shaped pristine NHM is achieved with 1D NHP embedded onto 2D nanosheets of NHS (Figure 1d–f, Figure S6, Supporting Information). The elemental mapping of TEM was then employed to confirm the elemental distribution of the Ni‐HITP in the NHM.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1b and Figure S5, Supporting Information, show that the NHP sample displays a particle size with an average diameter of around 50 nm, while for NHS, the nanosheets‐like Ni‐HITP is constructed in an interwoven pattern (Figure 1c). After the pore engineering of ball‐milling treatment, the size of NHP decreases obviously, [ 14 ] smaller than 10 nm, and meanwhile a unique Tostadas‐shaped pristine NHM is achieved with 1D NHP embedded onto 2D nanosheets of NHS (Figure 1d–f, Figure S6, Supporting Information). The elemental mapping of TEM was then employed to confirm the elemental distribution of the Ni‐HITP in the NHM.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the structure of the branch of the polymer dispersant adsorbed on the surface of the pigment particle formed a steric hindrance to prevent the aggregation of the pigment particle, thereby ensuring dispersion stability. 11 In addition, because the lin -PG-BzA 1 system had higher viscosity than that with only the BYK 190 dispersant, the use of lin -PG-BzA 1 as a synergist eventually disturbed the dispersing performance in the pigment solution.…”
Section: Resultsmentioning
confidence: 99%
“…Coagulation did not occur because the steric hindrance on the surface of pigment by hyperbranched structure of hb-PG-BzA 1 prevented the occulation of pigment particles during storage. 11,26 However, the lin-PG-BzA 1 system showed a decrease in viscosity of dispersion to 152.9 cps from the initial 378.0 cps, and the particle size was reversibly increased to 352.2 nm. This nding demonstrated that such a linear structure had low dispersing ability in the initial dispersion and was not effective for preventing particle aggregation by occulation during longterm storage.…”
Section: Topology-controlled Polymeric Synergists In Dispersionmentioning
confidence: 96%
See 1 more Smart Citation
“…Polyurethane (PU) is a versatile polymeric material which widely applied in coatings, adhesives, inks, textile and other fields. [1][2][3][4] In practical applications, polyurethane film surface will inevitably be damaged such as tears or scratches, affecting the performance and lifetime of the material, causing economic losses and waste of resources. Thus, self-healing polyurethane has been extensively studied during the past several years as a burgeoning functional material.…”
Section: Introductionmentioning
confidence: 99%